The Development of ‘CATRA’ Android-Based Learning Module with Gamification Approach for Students: A Research and Development on Learning Media - Jiny Dharma Ditha; Susanto Susanto; Hendri Ardianto; Vike Aprilianin Marwintaria Saputri; Dittha Winyana Putra; Candra Kusuma (International Journal of Science and Applied Science: Conference Series, 2024)
CATRA learning media is an Android-based learning module with a gamification approach. This study is motivated by the dominance of conventional methods in Senior High Schools, which shows the need for an innovative approach to learning. CATRA is designed as a multidimensional projection instrument to present the Four Noble Truths (Cattari Arya Saccani) material to create a more interactive and motivating learning environment. The methodology applied is research and development (R&D), with data collection procedures including observation, interviews, literature studies, and validation. The validation results from media experts, material experts, and Buddhist religious education teachers showed a very high level of feasibility, with a total score of 334, an average of 4.4, and a percentage of 88%. Based on these parameters, CATRA is classified as "Very feasible" and should be implemented in learning in senior high schools. Statistical analysis using the Paired Sample T Test showed a significant difference between learning outcomes before and after the use of media, with a calculated t value (-8.428) smaller than the t table (-2.2009) and a P value (0.00) smaller than 0.05. These findings indicate the effectiveness of CATRA in improving students' understanding of the material being taught. The significant difference between the average pre-test and post-test scores validates the positive impact of this learning media. Based on the study's results, further studies are recommended to explore the development of similar media for other learning materials to expand the scope and improve the effectiveness of educational innovation in a broader learning context.